Mineral project design using ABC methodology and dynamic simulation. - Cremonese, Dennis Travagini (2019)
This work presents two innovative ways to evaluate mining projects. The first is the Activity-Based Costing Approach in mining operations with a product mix. After analyzing and collecting data from an aggregate mine located in Brazil, a cost model was built, and from that, a cost management and analysis methodology of a mine is created. This work has the innovation advantages of using ABC as a tool for planning the operation of the mine, identifying the more profitable products. The second is the use of dynamic simulation in the early stage of Front End Loading (FEL) studies of a Mining Project. In the early stages the global availability (Number of hours a plant is available for production) and production (Number of hours a plant is actually operated with material) time of the process plant are normally assumed based on the experience of the study team. Understanding and defining the hours available at the early stages of the project are important for the future stages of the project, as drastic changes in work hours will impact the economics of the project at that stage. An innovative high-level dynamic modeling approach has been developed to assist in a fast evaluation of assumptions made by the study team. This model incorporates systems or equipment commonly used in mining projects from mine to product stockyard discharge after the process plant. This model includes subsystems that will simulate all the handling components, major processing plant systems required for a mining project. The output data provided by this high-level dynamic simulation approach will enhance the confidence level of engineering carried out during the early stage of the project. This work discusses the technical and economic advantages in using this approach and five test cases comparing with the standard techniques used in mining project FEL studies. At the end, it is concluded that the creation of a cost model to be applied in mining operations is a rewarding investment as it shows the profitable and unprofitable products, and that the use of dynamic simulation in the early stages is technically and economically advantageous.